Thermal and catalytic pyrolysis of automotive plastic wastes to diesel range fuel - Elly Olomo; Stephen Talai; Joseph Kiplagat; Egide Manirambona; Anthony Muliwa; Jasper Okino (Heliyon)
This study investigated the pyrolysis of automotive plastic wastes (APW) for the production of diesel-grade oil products using a modified calcium bentonite clay catalyst. The research aimed to optimize the process for maximum oil yield and diesel range organics yield. The APW was characterized by its chemical composition and physical properties and the optimal temperature and catalyst amount were determined for maximum oil yield and diesel range hydrocarbons. The results showed that the APW contained mixed Acrylonitrile Butadiene Styrene (ABS), High/Low Density Polyethylene (H/LDPE), Polypropylene (PP), Polystrene (PS) and fiberglass, with a large quantity of volatiles and ash. The average oil yield was higher in the catalytic process compared to that in the thermal process. Generally, higher temperature above 450 °C produced waxy oil, thus lower temperature favoured more Diesel Range Organics (DRO). Both processes yield similar yields of C8–C24 DRO, and in both cases, lower temperature favoured high yield of C8-C24 hydrocarbons. The catalyst significantly increased the yield of oil, but did not significantly increase C8–C24 DRO yield. The optimal conditions for a maximum oil yield of 78.6 % and DRO yield of 79.5 % was a temperature of 416 °C and 24.3 wt% clay. Thus, the modified calcium bentonite clay can be used to improve oil yield from pyrolysis of APW. The oil produced had properties such as calorific value (49.85 MJ/kg), flash point (113 °C) and total aromatics 3.55 area%, similar to those of commercial diesel, and comprised mostly of 2,4-Dimethyl-1-heptene (25.37 ± 2.01 %) of thermal and 2, 4 – Dimethyl – 1 – heptane (23.44 ± 2.42) in the catalytic process. The study suggests further research to explore different catalysts, maximization of both DRO and gasoline range organics, recover energy from residues, and conduct techno-economic assessments for plant-scale operations. Additionally, policies on the management of end-of-life vehicles should include provisions for stripping and segregation of plastic components by accredited providers for the purpose of plastics recycling.